A snowball against global warming: An alternative to the Kyoto protocol - Marco Verweij (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
Last November, in The Hague, international cooperation on global warming came to a grinding halt. But even if this United Nations conference had been an unqualified success, it would still not have made any difference to the world's climate. Only a radically different approach to international decision-making can save the world from over-heating. This alternative approach would be less statist and formalistic, and would focus more on the development of cheap forms of energy and technology that do not emit greenhouse gases. In this essay, it is asserted that the current international cooperation on climate change is doomed to fail, and a more realistic solution is described.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Förderung erneuerbarer Energien; Welt